Poverty, Health Iniquities, and Human Development are Global Issues - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The Online Brazilian Journal of Nursing joinned this international collaboration with journals from developed and developing countries to raise awareness in Brazilian nurses about the health iniquities and poverty and to point out the necessity of developing research to bring solutions, wellbeing, and health for all regardless, race/colour, age, gender, etc.
So, Online Brazilian Journal of Nursing created a new section: Poverty, Health Iniquities, and Human Development to point ou these issues.